Med politično propagando in verodostojnejšim poročanjem - Erjavec, Karmen (Javnost (Ljubljana), 2014)
During the campaign for elections to the EU Parliament interviews were carried out with 84 audience members in focus groups and in-depth interviews with 50 journalists /editors of influential Slovenian media. The results showed that Twitter neutrals those who have neither a negative nor a positive attitude toward Twitter predominated among the interviewed audience members. Twitter critics expressed highly negative attitudes toward Twitter and its use in journalism. Twitter enthusiasts regularly used Twitter and had positive attitudes toward it and its use in journalism. Journalists and editors were polarised in attitudes toward the use of Twitter in journalism. Twitter critics who had negative attitudes toward Twitter use in journalism considered it political propaganda, because journalists publish favourably the messages of those politicians who use Twitter. Arguments against the use of Twitter in journalism include the lack of news and discussion, elimination of journalists from communication between politicians and citizens and, conversely, the overburdening of journalists. Twitter enthusiasts had a favourable attitude towards the use of Twitter in journalism, arguing that it provides quick and cheap publication, brevity, transparency, self-promotion, and a greater reach.
Keywords: Slovenia; Slovenija; election; volitve; politična propaganda; mass media; množični mediji; journalism; novinarstvo; novinarji; družbena omrežja; socialna omrežja